Characterisation, health-promoting properties and food applications of anthocyanin-rich pigments of flowers from the Geraniaceae and Lamiaceae plant families - Duodu, Kwaku Gyebi (University of Pretoria, 2023)
Thesis (PhD (Food Science))--University of Pretoria, 2022.